Many Splendored Things Thinking Sex and Play - Paasonen, Susanna (Goldsmiths Press, 2018)
We all know that sex involves a quest for pleasure, that sexual palates vary across people's lifespans, and that playful experimentations play a key role in how people discover their diverse sexual turn-ons and turn-offs. Yet little attention has been paid to thinking through the interconnections of sex and play, sexuality and playfulness. In Many Splendored Things from Goldsmiths Press, Susanna Paasonen considers these interconnections. Paasonen examines the notions of playfulness and play as they shed light on the urgency of sexual pleasures, the engrossing appeal of sex, and the elasticity of sexual desires, and considers their connection to categories of identity. Drawing on a broad range of scholarship on sexuality, play, and the media, Paasonen moves from the conceptual to the concrete, examining advice literature on sexual play, the vernacular aesthetics of the Fifty Shades series, girls' experiences of online sexual role-playing, popular media coverage of age-play, and Jan Soldat's documentary films on BDSM culture. Paasonen argues that play in the realm of sexuality involves experimentation with what bodies can feel and do and what people may imagine themselves as doing, liking, and preferring. Play involves the exploration of different bodily capacities, appetites, orientations, and connections. Occasionally strained, dark, and even hurtful in the forms that it takes and the sensory intensities that it engenders, sex presses against previously perceived and imagined horizons of embodied potentiality. Play pushes sexual identifications into motion